Arabic Maqāmāt in Light of Foreign Antiquities (An Inductive Study): Literature and Criticism - AlBakar, Fahd Ibrahim Saad (Al-Ḍād Journal, 2023)
This research deals with an important subject, which takes a great place in the context of the linguistic and literary and criticism works which were the subject of foreign studies. This research is concerned with how non-Arab critics receive the ancient Arab prose. The research took the art of Arabic Maqāmāt as a model for it, as it touched the influence of this art which was famous and popularized by Badi’zaman al-Hamzani, Abu Bakr al-Hariri, and others. Their impact was evident in the global creativity map, whether in Persian, Spanish, Hebrew, or other literature. The importance of this research has been increased that it took care of the critical impact that these Arabic Maqāmāt left on foreigners where many of them pay great attention to it, as it also subjected to a distinguished critical standard, as in the case of one of the German orientalists who the search took him as evidence of that. Keywords: ancient Arabic prose - non-Arabic antiquities - influence and impact - Adam Metz